Pengaruh Desain Produk, Citra Merek, Dan Kualitas Produk Terhadap Keputusan Pembelian Brand Consina (Studi Kasus Pada Pecinta Alam di Kabupaten Malang) - Ferdiansah Pradana; Pardiman Pardiman; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Purchasing decisions are how consumers decide which alternative options to choose, and include decisions about what to buy, whether to buy or not, when to buy, where to buy, and how to pay for it. This study aims to determine how the influence of product design, brand image, and product quality on purchasing decisions. The research method used in the research is a quantitative approach. The population in this study is nature lovers in Malang Regency, for the determination of the number of samples using the malhotra formula amounted to 85 respondents. The data used in the study was primary data in the form of online questionnaire questionnaires using google forms. The data analysis methods used are: instrument test, multiple linear regression analysis, classical assumption test, coefficient of determination and hypothesis testing. The results showed that product design, brand image, and product quality had a partial positive effect on Consina's brand purchase decision. Keywords:Product Design, Brand Image, Product Quality, and Purchase Decision.